Direct Synthesis of Indolines via Cyclization of Tertiary Aryl Amines with Iodonium Ylides under Sole Visible Light Irradiation - Zhao, Yan‐Rui; Li, Lei; Xuan, Jun (Advanced synthesis & catalysis, 2023)
Herein we reported a direct synthesis series of indolines through cyclization of tertiary aryl amines with iodonium ylides. This cyclization reaction occurred under sole visible‐light irradiation at room temperature without the addition of any photocatalysts and additives. Preliminary mechanism studies revealed that an electron donor‐acceptor (EDA) complex between iodonium ylides and tertiary aryl amines should be formed during the reaction.